Connecting with the Australian Curriculum: Mathematics to integrate learning through the proficiency strands - Hurst, Chris (AAMT and MERGA, 2011)
A review of the rationale of the draft Australian Curriculum: Mathematics revealed that it has strong links with numeracy, making sense of mathematics, and making connections, both within mathematics itself, and between mathematics and everything else. There is a clear intent for teachers to use a constructivist approach with an emphasis on rich conceptual understanding and by teaching the content strands through the Proficiency strands, as opposed to solely the acquisition of procedural knowledge. This paper provides teachers with strategies for using an investigative approach to develop rich understandings of key number concepts and to enable their students to make connections with and within their mathematical knowledge.